Limitations in the Activity of Mobility at Age 6 Years After Difficult Birth at Term: Prospective Cohort Study. - van Iersel, Patricia A. M.; Algra, Annechien M.; Bakker, Saskia C. M.; Jonker, Arnold J. H.; Hadders-Algra, Mijna (Physical Therapy, 2016)
Background. A difficult birth at term (DBAT) may manifest as fetal acidosis and low Apgar scores and is often referred to as "perinatal asphyxia," especially when infants show signs of neonatal encephalopathy (NE). In contrast to DBAT resulting in moderate-to-severe NE, which is associated with neurodevelopmental disorders, little is known about the prognosis of less severe forms of DBAT, with or without NE. Objective. The purpose of this study was to evaluate the International Classification of Functioning, Disability and Health, Children & Youth Version activity "mobility" and other neurodevelopmental sequelae in infants with DBAT at age 6 years. Methods. The index cohort (n=62; 35 boys, 27 girls) consisted of consecutive term infants with DBAT based on clinical criteria in a Dutch nonacademic hospital from 1999 to 2005. Neonatal encephalopathy was assessed according to the Sarnat grading system and excluded infants with severe NE. The matched reference cohort (n=81; 49 boys, 32 girls) consisted of healthy term infants. The primary outcome at 6 years was limited mobility (Movement Assessment Battery for Children score ≤15th percentile). Secondary outcomes included learning and behavioral problems and the presence of minor neurological dysfunction. Results. Three children developed cerebral palsy and were excluded from analyses. Children with DBAT more often had limited mobility than children without DBAT (risk ratio [RR] = 2.44; 95% confidence interval [95% CI]= 1.16, 5.14). The risk of limited mobility rose with increasing severity of NE (mild NE: RR=3.38; 95% CI=1.40, 8.16; moderate NE: RR=4.00; 95% Cl=1.54, 10.40), and manual abilities especially were affected (RR=4.12; 95% CI=1.40, 12.14). Learning problems, need for physical therapy, and complex minor neurological dysfunction were more common in children with DBAT than in children without DBAT. Conclusions. Term infants who develop mild or moderate NE following DBAT are at increased risk for limited mobility at age 6 years. Routine monitoring of neuromotor development in these children is warranted.